Оптимізація пошуку в науковій бібліотеці на основі користувацьких оцінок - Думанський, Нестор (Видавництво Львівської політехніки, 2025)
The theses address the problem of optimizing the search for relevant scientific information amidst the increasing volume of publications. A concept for a scientific paper ranking system based on user feedback from the academic library, considering their reputation, is proposed. The mechanism for collecting evaluations, the principles for determining and adjusting user ratings based on the consensus of opinions, are described. The potential advantages of implementing such a system for enhancing search relevance, identifying high-quality works, and stimulating user interaction are considered. Prospects for further research in the development and testing of the proposed system are outlined.
Keywords: ранжування наукових праць; відгуки користувачів; репутація користувачів; оптимізація пошуку; наукова бібліотека; оцінювання наукового контенту